Genomics of Blastocrithidia, a trypanosomatid with all three stop codons reassigned - Nenarokova, Anna (Jihočeská univerzita, 2020)
This work describes genomic studies of Blastocrithidia, the trypanosomatid with all three stop codons encoding amino acids and the only known euglenozoan with non-standard nuclear genetic code. We describe unique genomic features of Blastocrithidia and the sister clade "Jaculum", and discuss possible mechanisms of translation termination with ambiguous stop codons and the evolutionary path that may have established this system.
Genomics of Blastocrithidia, a trypanosomatid with all three stop codons reassigned
Keywords: genetic code reassignment; trypanosomatids; stop codons; translation termination; genetic code reassignment; trypanosomatids; stop codons; translation termination